Antecedents of intention to use sharing economy services in the latter phase of COVID-19 - Curina, Ilaria; De Cicco, Roberta; Francioni, Barbara; Cioppi, Marco; Rotoloni, Sofia; Diotallevi, Jennifer (Piccola Impresa / Small Business, 2024)
Purpose. The sharing economy presents a crucial opportunity for companies, especially for small and medium enterprises (SMEs). Through collaborative partnerships and sharing economy services, these companies can overcome limited resources, fostering growth and competitive advantage. However, identifying key variables that attract users and drive the usage of sharing economy services is essential for their success. The objective of this study is to analyse the impact of four categories of antecedents (i.e., COVID-19 related, technical, individual and personal, and environmental variables) on consumers’ intention to use sharing economy services during an advanced phase of the COVID-19 pandemic. Design/methodology/approach. A total of 316 respondents participated in an online survey and Structural Equation Modelling (SEM) was used to analyse the proposed research model and test the hypotheses. Findings. A positive and significant influence of technical (i.e., service quality), individual and personal (i.e., perceived value and perceived usefulness), and environmental antecedents (i.e., environmental orientation) on the intention to use sharing economy services has been detected, while a non-significant impact of COVID-19 related factors (i.e., fear of COVID-19, uncertainty of COVID-19, and perceived risk of travelling during COVID-19) has been identified. However, a significant moderating effect of fear of COVID-19 on the relationship between perceived value and the intention to use sharing economy services has been confirmed. Practical and Social implications. The paper provides possible strategies that sharing economy providers could adopt to enhance their customers’ intention to continue using their services. Originality of the study. The paper seeks to fill different research gaps identified in the extant literature by shedding light on the effects of specific categories of predictors on the consumers’ intention to use sharing economy activities during an advanced phase of the pandemic crisis.